A special purpose company as an alternative form of conducting development projects - Szreder, Jaroslaw (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The article presents an original model of organizing financing of residential development projects using special purpose company (SPC). In the face of the growing demand for effective risk management and capital protection mechanisms, SPCs are becoming an important tool in the implementation of development projects, which are usually characterized by a high level of risk and a long period of return on investment. The author discusses the essence and functioning of SPCs, presents the possibilities of their application in the development industry and analyzes the key aspects of choosing the organizational and legal form for this type of projects. Using research methods such as participant observation based on his experience and analysis of professional literature and current legislation, the author seeks an answer to the research problem posed, which is as follows: can the proposed model of financing SPCs in the implementation of development projects be effectively used in the current market and legal conditions. Based on the conducted research and analyses, the author draws conclusions that the presented model of financing development projects through a special purpose vehicle can be effectively used in the current market and legal conditions.